A 0.55-V 0.1oC-Accuracy All-CMOS Temperature Sensor for Implanted Devices - de Lima, Jader (Symposium on Integrated Circuits and Systems Design (SBCCI); 2020: Anais do XXXIII Symposium on Integrated Circuits and Systems Design, 2020)
A compact ultra-low power low-voltage all-CMOS temperature sensor for implanted devices is presented. Besides the analog front-end (AFE), the sensor topology incorporates a ring oscillator and a counter. The AFE performs a PWM-based voltage-to-time conversion of a temperature-modulated pulsewidth for the subsequent quantization. A pair of temperature cells delivers both reference and CTAT voltages for pulsewidth modulation. Intended for body-temperature measurements, the sensor is designed according to a standard 0.18μm CMOS, with theoretical analysis backed up by SPICE data over the range [36°C–41°C]. Owing to structurally-alike temperature cores, a design that preserves its reliability across process corners (FF fast-fast, FS fast-slow, SS slow-slow and SF slow-fast) is achieved, making trimming of temperature voltages and frequency unnecessary. The circuit estimated area is 0.003 mm 2 and dissipates typically 365nW, at V DD =0.55V. The temperature elements consume 100pW, which favors multi-channel versions of the sensor. After 2-point calibration, the overall inaccuracy is 0.1°C for TT, FF and SF cases, while 0.2°C and 0.3°C at SS and FS corners, respectively. The approach is easily scalable and therefore suitable to progress into more advanced CMOS nodes.